2018
DOI: 10.2147/ppa.s166523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Health Belief Model-based education program on patients’ belief, physical activity, and serum uric acid: a randomized controlled trial

Abstract: ObjectiveWe aimed to investigate the effect of a Health Belief Model (HBM)-based education program on the perception scores of 5 HBM domains, physical activity, and serum uric acid (SUA) among asymptomatic hyperuricemia (AHU) patients in a randomized controlled trial.MethodsOne hundred and ninety-three AHU patients were involved in this prospective experimental interventional study in Shanghai, China. Subjects were randomly divided into interventional or control group. The educational program was designed base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 26 publications
7
27
0
2
Order By: Relevance
“…Patients with a history of chronic disease (hypertension, diabetes, and stroke) were 1.4 times more likely to maintain regular PA in our study, which differs from the findings of Armstrong et al 39 This may be because individuals in our study with chronic disease history had more frequent visits to healthcare providers and received more education about the benefits of PA. We found that patients who knew the benefits of PA were 4 times more likely to maintain PA. This is similar to results from a previous study, which showed that an awareness of the benefits of PA is helpful in encouraging patients to establish PA. 40 Years of CHD was negatively associated with maintaining regular PA. An additional year of CHD lowered the odds of maintaining regular PA by 4% ( P = .02). This might be explained by a reduction in the capacity for PA associated with progression of CHD.…”
Section: Discussionmentioning
confidence: 93%
“…Patients with a history of chronic disease (hypertension, diabetes, and stroke) were 1.4 times more likely to maintain regular PA in our study, which differs from the findings of Armstrong et al 39 This may be because individuals in our study with chronic disease history had more frequent visits to healthcare providers and received more education about the benefits of PA. We found that patients who knew the benefits of PA were 4 times more likely to maintain PA. This is similar to results from a previous study, which showed that an awareness of the benefits of PA is helpful in encouraging patients to establish PA. 40 Years of CHD was negatively associated with maintaining regular PA. An additional year of CHD lowered the odds of maintaining regular PA by 4% ( P = .02). This might be explained by a reduction in the capacity for PA associated with progression of CHD.…”
Section: Discussionmentioning
confidence: 93%
“…The results showed that group training by HBM led to an improvement in the scores of all model's constructs and the level of physical activity. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…We will use an adapted version of the HBM (Figure 1) as a basis for a 'best fit' framework synthesis (BFFS) approach to analyse and synthesise qualitative evidence (Booth 2015; Booth 2016; Carroll 2013). The HBM has been used to explore health beliefs and physical activity in a range of populations, Gristwood 2011; Hosseini 2017; Kasser 2012, and informed the development of physical activity interventions (Shao 2018). The selection of the Cochrane Database of Systematic Reviews HBM drew on the Cochrane Methods guidance for selecting a theory for complex intervention reviews (Noyes 2015); the model has the ability to consider complex interventions and has been validated and used in other systematic reviews.…”
Section: Data Synthesismentioning
confidence: 99%